2003
DOI: 10.1016/s0304-3959(03)00297-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of odors on pain perception: deciphering the roles of emotion and attention

Abstract: Emotions have been shown to alter pain perception, but the underlying mechanism is unclear since emotions also affect attention, which itself changes nociceptive transmission. We manipulated independently direction of attention and emotional state, using tasks involving heat pain and pleasant and unpleasant odors. Shifts in attention between the thermal and olfactory modalities did not alter mood or anxiety. Yet, when subjects focused attention on the pain, they perceived it as clearly more intense and somewha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
230
7
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(270 citation statements)
references
References 43 publications
25
230
7
4
Order By: Relevance
“…Second, we found no effects of distraction on pain affect. This is not consistent with previous studies that have demonstrated effects on both pain affect and intensity [41,42,51], but is similar to studies which have shown that the manipulation of attention clearly alters pain intensity, but influences pain affect to a far lesser degree [29,30,61]. It is possible that our pain affect measure was less sensitive and therefore not reached significance.…”
contrasting
confidence: 68%
See 2 more Smart Citations
“…Second, we found no effects of distraction on pain affect. This is not consistent with previous studies that have demonstrated effects on both pain affect and intensity [41,42,51], but is similar to studies which have shown that the manipulation of attention clearly alters pain intensity, but influences pain affect to a far lesser degree [29,30,61]. It is possible that our pain affect measure was less sensitive and therefore not reached significance.…”
contrasting
confidence: 68%
“…Such an explanation is however unlikely. Positive affect mainly alters pain affect, not pain intensity [61], and we observed the reverse. Finally, the differential effects of motivation on distraction effectiveness for high and low catastrophizers are interesting, but further research is necessary to replicate our findings.…”
mentioning
confidence: 40%
See 1 more Smart Citation
“…Attention can also modulate pain (Bantick et al 2002) and exacerbation of pain by anxiety is associated with activity in the hippocampal network (Ploghaus et al 2001). Thus, cognitive and emotional factors can affect unpleasantness (or pain distress) without changing the intensity of pain (Villemure and Bushnell 2002;Villemure et al 2003). The ACC, along with the periaqueductal grey (PAG), amygdala, and anterior insula, plays a key role in how mood and pain modulate one another (Weich and Tracey 2009).…”
Section: Biological Mechanisms Of Physical Pain Processingmentioning
confidence: 99%
“…To induce emotions, pictures (Junghofer et al, 2006), films (Weisenberg et al, 1998), odours (Villemure et al, 2003), music (Robazza et al, 1994;Koelsch et al, 2006), mental imagery (Holmes and Mathews, 2005) and respiration (Philippot et al, 2002), hypnosis (Rainville et al, 2005) and games have been used. During games a strong identification with the played role identity occurs (de Quervain et al, 2004;Singer et al, 2006).…”
Section: Introductionmentioning
confidence: 99%